Aplikasi Buku Pintar Ruang Angkasa sebagai Media Pembelajaran berbasis Augmented Reality - Yusuf, Farid Maulana; Dijaya, Rohman; Rosid, Mochamad Alfan; Taurusta, Cindy (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
Space learning is still dominated by traditional books, but is often considered monotonous because it only presents static text and images. This study aims to develop a Smart Space Book based on Augmented Reality (AR) as an interactive learning media to present space concepts more visually and attractively. The method used is the Multimedia Development Life Cycle (MDLC), which consists of six stages: conceptualization, application design, material collection, application development, application testing, and application distribution. This application was developed using Unity 3D on Android devices with the marker-based tracking method, which displays 3D objects such as the Solar System, Galaxy, Stars, and Space equipped with interactive explanatory materials. Testing was carried out through black box testing to assess system functionality as well as usability tests and field studies at Aisyiyah Bustanul Athfal Kindergarten. The results of our findings are in the form of a Smart Space Book application based on Augmented Reality (AR), which can function well according to the design that has been determined and is applied as an interactive AR-based learning media. The test results of this application provide an alternative in presenting space material more visually and interactively and have the potential to be applied at various levels of education.